(E)-4-Methyl-N′-[(4-oxo-4H-chromen-3-yl)methylidene]benzohydrazide - Ishikawa, Yoshinobu (International Union of Crystallography, 2014)
In the title chromone-tethered benzohydrazide derivative, C(18)H(14)N(2)O(3), the 4H-chromen-4-one and the –CH=N–NH–CO– units are each essentially planar, with the largest deviations from thei planes being 0.052 (2) and 0.003 (2) Å, respectively. The dihedral angles between the 4H-chromen-4-one and the –CH=N–NH–CO– units, the 4H-chromen-4-one unit and the benzene ring of the 4-tolyl group, and the benzene ring of the 4-tolyl group and the –CH=N–NH–CO– unit are 8.09 (7), 9.94 (5) and 17.97 (8)°, respectively. In the crystal, the molecules form two types of centrosymmetric dimers: one by N—H⋯O hydrogen bonds and the other by π–π stacking interactions between the 4H-chromen-4-one unit and the 4-tolyl group [centroid–centroid distance = 3.641 (5) Å]. These dimers form one-dimensional assemblies extending along the a-axis direction. Additional π–π stacking interactions between two 4H-chromen-4-one units [centroid–centroid distance = 3.591 (5) Å] and two 4-tolyl groups [centroid–centroid distance = 3.792 (5) Å] organize the molecules into a three-dimensional network.